Potassium Deficiency in Cotton: Causes, Symptoms, and Considerations: SS-AGR-479/AG475, 1/2024 - Singh, Kulpreet; Singh, Hardeep; Omara, Peter; Nwosu, Nkem J.; Bearden, Jennifer; Singh, Ravinder; Sharma, Lakesh K. (EDIS, 2024)
The purpose of this publication is to inform cotton producers, Extension agents, crop advisors, and consultants about the role, deficiency, and management of potassium in cotton production. Written by Kulpreet Singh, Hardeep Singh, Peter Omara, Nkem J. Nwosu, Jennifer Bearden, Ravinder Singh, and Lakesh K. Sharma, and published by the UF/IFAS Agronomy Department, January 2024.